Circulating microbiome in patients with portal hypertension. (31st December 2022) - Gedgaudas, Rolandas; Bajaj, Jasmohan S; Skieceviciene, Jurgita; Varkalaite, Greta; Jurkeviciute, Gabija; Gelman, Sigita; Valantiene, Irena; Zykus, Romanas; Pranculis, Andrius; Bang, Corinna; Franke, Andre; Schramm, Christoph; et al.
ABSTRACT: Portal hypertension (PH) in liver cirrhosis leads to increased gut permeability and the translocation of bacteria across the gut–liver axis. Microbial DNA has recently been detected in different blood compartments; however, this phenomenon has not been thoroughly analyzed in PH. This study aimed to explore circulating bacterial DNA signatures, inflammatory cytokines, and gut permeability markers in different blood compartments (peripheral and hepatic veins) of patients with cirrhosis and PH. The 16S rRNA blood microbiome profiles were determined in 58 patients with liver cirrhosis and 46 control patients. Taxonomic differences were analyzed in relation to PH, liver function, inflammatory cytokines, and gut permeability markers. Circulating plasma microbiome profiles in patients with cirrhosis were distinct from those of the controls and were characterized by enrichment of Comamonas, Cnuella, Dialister, Escherichia/Shigella, and Prevotella and the depletion of Bradyrhizobium, Curvibacter, Diaphorobacter, Pseudarcicella, and Pseudomonas . Comparison of peripheral and hepatic vein blood compartments of patients with cirrhosis did not reveal differentially abundant taxa. Enrichment of the genera Bacteroides, Escherichia/Shigella, and Prevotella was associated with severe PH (SPH) in both blood compartments; however, circulating microbiome profiles could not predict PH severity. Escherichia/Shigella and Prevotella abundance was correlated with IL-8 levels in the hepatic vein. In conclusion, we demonstrated a distinct circulating blood microbiome profile in patients with cirrhosis, showing that specific bacterial genera in blood are marginally associated with SPH, Model for End-Stage Liver Disease score, and inflammation biomarkers; however, circulating microbial composition failed to predict PH severity.